Engineers’ abilities influence spatial perspective changing - Paola Verde; Gregorio Angelino; Francesco Piccolo; Paolo Corrazzo; Laura Piccardi; Raffaella Nori (International Journal of Engineering Education, 2019)
In this paper we studied the effect of engineering expertise in providing directional judgments. We asked two groups of people, engineers and non-engineers, to observe and memorize five maps, each including a four-point path, for 30 sec. The path was then removed and the participants had to provide two directional judgments: aligned (the imagined perspective on the task was the same as the one just learned), and counter-aligned (the imagined perspective on the task was rotated by 180°). Our results showed that engineers are equally able to perform aligned and counter-aligned directional judgments. The alignment effect due to the distance from the learning perspective was, in fact, shown only by non-engineers. Results are discussed considering engineering both learning expertise and specific predisposition.